POR UMA PROFISSIONALIZAÇÃO EDUCATIVA: um ensaio em defesa da escola pública e da valorização da docência - Arnosti, Rebeca Possobom [UNESP]; de Souza Neto, Samuel [UNESP] (Curriculo sem Fronteiras, 2024)
The professionalization of teaching born as a movement that proposes to overcome school failure, making schools better places to teach and learn. If, on the one hand, professionalization revolutionized the way we understand the school, teaching, teacher training and the production of knowledge in the Pedagogy´s field; on the other hand, limits and criticism are linked to this movement, which is often associated with the precariousness of teaching, the increase in assignments and pressure on teachers without their due return. Thus, we ask: four decades after the dissemination of the concept of professionalization, is it still valid for us to support and think about improving the quality of education and teacher training? Faced with this issue, we performed a synthesis on the origins of the movement, demarcated the main contributions and limits associated with it and, finally, defended our position, assuming the defense for an educational professionalization, which has as bases: the professional culture, the commitment to education, autonomy as a political and social achievement and multidisciplinary responses to the challenges experienced in the education´s field.
POR UMA PROFISSIONALIZAÇÃO EDUCATIVA: um ensaio em defesa da escola pública e da valorização da docência
Keywords: educational professionalization; professional culture; teacher professional development; teacher training